Hubungan Penggunaan Teknologi Artificial Intelligence Terhadap Kemampuan Berpikir Kritis Mahasiswa Tadris Matematika Fakultas Ilmu Tarbiyah Uin Raden Mas Said Surakarta Angkatan 2022 - Yuli Astuti Intan Sagetria; Wiwin Astuti (GLOBAL SCIENTS PUBLISHER, 2025)
Critical thinking is a crucial skill in education, especially in mathematics, as it contributes to deeper understanding and effective problem-solving abilities. However, students often rely on AI-based technologies such as Photomath and ChatGPT without fully understanding the underlying concepts, which may hinder the development of their critical thinking skills. This study aims to: (1) analyze how Artificial Intelligence is used by Mathematics Education students at UIN Raden Mas Said Surakarta in the 2024/2025 academic year; (2) analyze the level of students' critical thinking abilities; and (3) determine whether there is a relationship between the use of Artificial Intelligence technology and the critical thinking abilities of Mathematics Education students at the Faculty of Tarbiyah and Teacher Training, UIN Raden Mas Said Surakarta. This research employs a quantitative method with a correlational approach. The population consists of all 2022 cohort students in the Mathematics Education Study Program at UIN Raden Mas Said Surakarta, totaling approximately 85 students. The sample was selected using cluster random sampling, with a total of 28 respondents. Data were collected through questionnaires, tests, and documentation, focusing on the use of AI technology and students' critical thinking levels. Data analysis was conducted using the product-moment correlation method with SPSS version 25.00, including tests for validity, reliability, normality, and hypothesis testing to measure the relationship between AI usage and critical thinking skills. The research results show that 1) Students actively use AI applications such as Photomath and ChatGPT in their academic activities. Based on questionnaire results from 28 respondents, the average scores of AI usage were categorized as moderate to high in frequency (67.64), purpose (70.54), and independence (68.82). This indicates that students are quite active in using AI technology, particularly in understanding materials, solving problems, and finding solutions to mathematical questions. However, such intense usage also suggests a tendency toward dependency on these technologies. 2) Students' critical thinking ability is generally in the moderate category, with an average score of 70.93. About 57.1% of students fall into the moderate category, 32.1% in the high category, and 10.8% in the low category. Students show fairly good performance in the aspects of clarification, assessment, and inference, although they still struggle with the strategy/tactics aspect, indicating the need for learning reinforcement that supports reflective and systematic thinking processes. 3) Based on the results of data analysis using the Pearson correlation test, the correlation coefficient (r) was found to be -0.070 with a significance value (Sig. 1-tailed) of 0.363. Since the significance value is greater than 0.05, it indicates that there is no relationship between the use of AI and the level of critical thinking